A 3D Opened Hollow Photothermal Evaporator for Highly Efficient Solar Steam Generation. Issue 7 (30th April 2022) - Chen, Yiquan; Wang, Yida; Xu, Jie; Ibn Raihan, Md Rubaiet; Guo, Bin; Yang, Guang; Li, Mengyuan; Bao, Haifeng; Xu, Haolan
Abstract : Herein, using hierarchical porous CuS–cellulose composite as photothermal materials, a 3D opened hollow photothermal evaporator is designed and fabricated to target high solar evaporation rates. Such a unique structure not only imparts the solar evaporator with an efficient water evaporation by minimizing energy loss, introducing cold evaporation surfaces for drawing additional energy from the bulk water and surrounding air, but also fully activates evaporation on both inner and outer evaporation surfaces, thus delivering superior evaporation rates compared to the enclosed evaporators. Moreover, under convective flow, this special structure effectively promotes the escape of vapor inside the evaporator to avoid the vapor accumulation, further enhancing the evaporation on inner evaporation surfaces, thus improving the evaporation rate up to11.911 kg m −2 h −1 under a convective flow rate of 4.0 m s −1 and 1.0 sun irradiation. The operability of the as‐prepared solar evaporator under natural environmental conditions is examined by outdoor evaporation tests. The obtained solar evaporator is demonstrated to be applicable for generating clean water from model seawater and dye wastewater. An impetus for promoting practical application of solar steam generation in seawater desalination and wastewater purification is provided. Abstract : A 3D opened hollow photothermal evaporator is designed using hierarchically porous CuS–cellulose composite as photothermal materials. This special structure not only imparts the solar evaporator with efficient water evaporation by minimizing energy loss, introducing cold evaporation surfaces for harvesting additional energy from surrounding environment, but also fully activates the evaporation on inner evaporation surfaces, thus delivering extremely high evaporation rates.